Download presentation
Presentation is loading. Please wait.
Published byHarold Lee Modified over 8 years ago
1
Let us discuss the harmonic oscillator
2
E = T + V = ½mv 2 + ½kx 2
3
Let us discuss the harmonic oscillator E = T + V = ½mv 2 + ½kx 2 H = p x 2 /2m + ½kx 2
4
Let us discuss the harmonic oscillator E = T + V = ½mv 2 + ½kx 2 H = p x 2 /2m + ½kx 2 By a change of variables
5
Let us discuss the harmonic oscillator E = T + V = ½mv 2 + ½kx 2 H = p x 2 /2m + ½kx 2 By a change of variables x = q(mω) -½ ω = (k/m) ½
6
Let us discuss the harmonic oscillator E = T + V = ½mv 2 + ½kx 2 H = p x 2 /2m + ½kx 2 By a change of variables x = q(mω) -½ ω = (k/m) ½ We get a rather neater equation for the Hamiltonian
7
Let us discuss the harmonic oscillator E = T + V = ½mv 2 + ½kx 2 H = p x 2 /2m + ½kx 2 By a change of variables x = q(mω) -½ ω = (k/m) ½ We get a rather neater equation for the Hamiltonian H = ½ω(p 2 + q 2 )
9
Let’s now consider this set of commutators
10
H = ½ω(p 2 + q 2 ) Let’s now consider this set of commutators NB that I have set ħ = 1 to simplify the relations
11
H = ½ω(p 2 + q 2 ) Let’s now consider this set of commutators NB that I have set ħ = 1 to simplify the relations [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq
12
H = ½ω(p 2 + q 2 ) Let’s now consider this set of commutators NB that I have set ħ = 1 to simplify the relations [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq From this set of quantum mechanical definitions
13
H = ½ω(p 2 + q 2 ) Let’s now consider this set of commutators NB that I have set ħ = 1 to simplify the relations [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq From this set of quantum mechanical definitions We can invent a couple of B-type operators
14
H = ½ω(p 2 + q 2 ) Let’s now consider this set of commutators NB that I have set ħ = 1 to simplify the relations [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq From this set of quantum mechanical definitions We can invent a couple of B-type operators ie operators that follow the form
15
H = ½ω(p 2 + q 2 ) Let’s now consider this set of commutators NB that I have set ħ = 1 to simplify the relations [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq From this set of quantum mechanical definitions We can invent a couple of B-type operators ie operators that follow the form AB – BA = kB
17
[q,p] = i [H,q] = ω(-ip) [H,p] = ωiq
18
AB – BA = kB [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq F + = q + ip
19
AB – BA = kB [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq F + = q + ip [H, F + ] = [H,q] + i[H,p]
20
AB – BA = kB [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq F + = q + ip [H, F + ] = [H,q] + i[H,p] = ω(–ip) + iω(iq)
21
AB – BA = kB [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq F + = q + ip [H, F + ] = [H,q] + i[H,p] = ω(–ip) + iω(iq) = ω(–ip – q) = – ωF +
22
AB – BA = kB [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq F + = q + ip [H, F + ] = [H,q] + i[H,p] = ω(–ip) + iω(iq) = ω(–ip – q) = – ωF + [H, F + ] = –ωF +
23
AB – BA = kB [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq F + = q + ip [H, F + ] = [H,q] + i[H,p] = ω(–ip) + iω(iq) = ω(–ip – q) = – ωF + [H, F + ] = –ωF + and [H, F – ] = +ωF –
24
[H, F + ] = – ωF +
25
HF + – F + H = – ωF +
26
[H, F + ] = – ωF + HF + – F + H = – ωF + Now let’s operate with both sides of this expression on a particular eigenfunction E n
27
[H, F + ] = – ωF + HF + – F + H = – ωF + Now let’s operate with both sides of this expression on a particular eigenfunction E n ie the n th eigenfunction defined by
28
[H, F + ] = – ωF + HF + – F + H = – ωF + Now let’s operate with both sides of this expression on a particular eigenfunction E n ie the n th eigenfunction defined by H E n = E n E n
29
[H, F + ] = – ωF + HF + – F + H = – ωF + Now let’s operate with both sides of this expression on a particular eigenfunction E n ie the n th eigenfunction defined by H E n = E n E n H F + E n – F + H E n = – ωF + E n
30
[H, F + ] = – ωF + HF + – F + H = – ωF + Now let’s operate with both sides of this expression on a particular eigenfunction E n ie the n th eigenfunction defined by H E n = E n E n H F + E n – F + H E n = – ωF + E n H F + E n – E n F + E n = – ωF + E n
31
[H, F + ] = – ωF + HF + – F + H = – ωF + Now let’s operate with both sides of this expression on a particular eigenfunction E n ie the n th eigenfunction defined by H E n = E n E n H F + E n – F + H E n = – ωF + E n H F + E n – E n F + E n = – ωF + E n H F + E n = (E n – ω) F + E n
32
[H, F + ] = – ωF + HF + – F + H = – ωF + Now let’s operate with both sides of this expression on a particular eigenfunction E n ie the n th eigenfunction defined by H E n = E n E n H F + E n – F + H E n = – ωF + E n H F + E n – E n F + E n = – ωF + E n H F + E n = (E n – ω) F + E n So F + has operated on E n to produce a new eigenfunction with eigenvalue E n – ω
33
EnEn EnEn
34
EnEn E n – ω EnEn
35
EnEn E n – 2ω EnEn
36
EnEn E n – ω E n – 2ω EnEn Let’s ladder down till we get to the last eigenvalue at which a next application of F + would produce an eigenstate with negative energy which we shall posutlate is not allowed and so F + must annihilate this last eigenstate ie F + E ↓ = 0
37
EnEn E n – ω E n – 2ω E↓E↓ EnEn Let’s ladder down till we get to the last eigenvalue at which a next application of F + would produce an eigenstate with negative energy which we shall posutlate is not allowed and so F + must annihilate this last eigenstate ie F + E ↓ = 0 Aaaaghhhhh…… F+F+ E↓E↓
38
F + F – = (q + ip)(q – ip)
39
= q 2 – iqp + ipq +p 2
40
F + F – = (q + ip)(q – ip) = q 2 – iqp + ipq +p 2 = q 2 – i[q,p] + p 2
41
F + F – = (q + ip)(q – ip) = q 2 – iqp + ipq +p 2 = q 2 – i[q,p] + p 2 = q 2 + p 2 + 1
42
F + F – = (q + ip)(q – ip) = q 2 – iqp + ipq +p 2 = q 2 – i[q,p] + p 2 = q 2 + p 2 + 1 F + F – – 1 = q 2 + p 2
43
F + F – = (q + ip)(q – ip) = q 2 – iqp + ipq +p 2 = q 2 – i[q,p] + p 2 = q 2 + p 2 + 1 F + F – – 1 = q 2 + p 2 H = ½ ω(q 2 + p 2 )
44
F + F – = (q + ip)(q – ip) = q 2 – iqp + ipq +p 2 = q 2 – i[q,p] + p 2 = q 2 + p 2 + 1 F + F – – 1 = q 2 + p 2 H = ½ ω(q 2 + p 2 ) H = ½ ω(F + F – – 1)
45
F + F – = (q + ip)(q – ip) = q 2 – iqp + ipq +p 2 = q 2 – i[q,p] + p 2 = q 2 + p 2 + 1 F + F – – 1 = q 2 + p 2 H = ½ ω(q 2 + p 2 ) H = ½ ω(F + F – – 1) H = ½ ω(F – F + + 1)
46
F + F – = (q + ip)(q – ip) = q 2 – iqp + ipq +p 2 = q 2 – i[q,p] + p 2 = q 2 + p 2 + 1 F + F – – 1 = q 2 + p 2 H = ½ ω(q 2 + p 2 ) H = ½ ω(F + F – – 1) H = ½ ω(F – F + + 1) H E ↓ = ½ ω(F – F + + 1) E ↓
47
F + F – = (q + ip)(q – ip) = q 2 – iqp + ipq +p 2 = q 2 – i[q,p] + p 2 = q 2 + p 2 + 1 F + F – – 1 = q 2 + p 2 H = ½ ω(q 2 + p 2 ) H = ½ ω(F + F – – 1) H = ½ ω(F – F + + 1) H E ↓ = ½ ω(F – F + + 1) E ↓ F + E ↓ = 0
48
F + F – = (q + ip)(q – ip) = q 2 – iqp + ipq +p 2 = q 2 – i[q,p] + p 2 = q 2 + p 2 + 1 F + F – – 1 = q 2 + p 2 H = ½ ω(q 2 + p 2 ) H = ½ ω(F + F – – 1) H = ½ ω(F – F + + 1) H E ↓ = ½ ω(F – F + + 1) E ↓ F + E ↓ = 0 H E ↓ = ½ ω E ↓ Zero Point Energy
49
F + F – = (q + ip)(q – ip) = q 2 – iqp + ipq +p 2 = q 2 – i[q,p] + p 2 = q 2 + p 2 + 1 F + F – – 1 = q 2 + p 2 H = ½ ω(q 2 + p 2 ) H = ½ ω(F + F – – 1) H = ½ ω(F – F + + 1) H E ↓ = ½ ω(F – F + + 1) E ↓ F + E ↓ = 0 H E ↓ = ½ ω E ↓ Zero Point Energy E (v) = ω (v + ½)
52
They are F ± = q ± ip By inspection we can show that [H, F + ] = – ωF + [H, F – ] = + ωF – These are of the form [A, B] = kB So the Fs are B-type operators
53
Now H can be factorised as H = ½ω(F + F – – 1) H = ½ω(F – F + + 1) H = ½ω(F + F – – 1) H = ½ω(F – F + + 1)
54
Now H can be factorised as H = ½ω(F + F – – 1) H = ½ω(F – F + + 1) H{F + E n } = (E n – ω){F + E n } H{F – E n } = (E n – ω){F – E n }
55
Now H can be factorised as H F + E n = ½ω(F + F – – 1) F + E n H{F + E n } = (E n – ω){F + E n } H{F – E n } = (E n – ω){F – E n }
56
A A’ = A’ A’ AB A’ – BA A’ = kB A’ AB A’ – BA’ A’ = kB A’ A{B A’ } = (A’ + k){B A’ }
57
Let us discuss the harmonic oscillator E = T + V = ½m 2 + ½kx 2 H = p 2 /2m + ½kx 2 By a change of variables x = q(mω) -½ ω = (k/m) ½ We get a rather neater equation for the Hamiltonian H = ½ω(p 2 + q 2 )
58
Let us discuss the harmonic oscillator E = T + V = ½m 2 + ½kx 2 H = p 2 /2m + ½kx 2 By a change of variables x = q(mω) -½ ω = (k/m) ½ We get a rather neater equation for the Hamiltonian H = ½ω(p 2 + q 2 )
59
Let’s now consider this set of commutators NB that I have set ħ = 1 to simplify the relations [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq From this set of quantum mechanical definitions We can invent a couple of B-type operators ie one that follows the form AB – BA = ±kB
60
[q,p] = i [H,q] = ω(–ip) [H,p] = ω(iq) From this set of quantum mechanical definitions We can invent a couple of B-type operators ie one that follows the form AB – BA = ±kB F + = q + ip [H, F + ] = [H,q] + i[H,p] = ω(–ip) + iω(iq) = ω(–ip – q) = – ωF + [H, F + ] = –ωF + and [H, F – ] = +ωF –
61
[H, F + ] = – ωF + HF + – F + H = – ωF + Operate on a particular eigenfunction E n ie the n th eigenfunction defined by H E n = E n E n with both sides H F + E n – F + H E n = – ωF + E n H F + E n – E n F + E n = – ωF + E n H F + E n = (E n – ω) F + E n
62
They are F ± = q ± ip By inspection we can show that [H, F + ] = – ωF + [H, F – ] = + ωF – These are of the form [A, B] = kB So the Fs are B-type operators
63
Now H can be factorised as H = ½ω(F + F – – 1) H = ½ω(F – F + + 1) H = ½ω(F + F – – 1) H = ½ω(F – F + + 1)
64
Now H can be factorised as H = ½ω(F + F – – 1) H = ½ω(F – F + + 1) H{F + E n } = (E n – ω){F + E n } H{F – E n } = (E n – ω){F – E n }
65
Now H can be factorised as H F + E n = ½ω(F + F – – 1) F + E n H{F + E n } = (E n – ω){F + E n } H{F – E n } = (E n – ω){F – E n }
66
A A’ = A’ A’ AB A’ – BA A’ = kB A’ AB A’ – BA’ A’ = kB A’ A{B A’ } = (A’ + k){B A’ }
68
H = ½ω(p 2 + q 2 ) Let’s now consider this set of commutators NB that I have set ħ = 1 to simplify the relations [q,p] = i [H,q] = ω(-ip) [H,p] = ωiq From this set of quantum mechanical definitions We can invent a couple of B-type operators ie one that follows the form AB – BA = ±kB
69
[q,p] = i [H,q] = ω(–ip) [H,p] = ω(iq) From this set of quantum mechanical definitions We can invent a couple of B-type operators ie one that follows the form AB – BA = ±kB F + = q + ip [H, F + ] = [H,q] + i[H,p] = ω(–ip) + iω(iq) = ω(–ip – q) = – ωF + [H, F + ] = –ωF + and [H, F – ] = +ωF –
70
[H, F + ] = – ωF + HF + – F + H = – ωF + Operate on a particular eigenfunction E n ie the n th eigenfunction defined by H E n = E n E n with both sides H F + E n – F + H E n = – ωF + E n H F + E n – E n F + E n = – ωF + E n H F + E n = (E n – ω) F + E n
71
EnEn E n – ω E n – 2ω E↓E↓ EnEn nn Let’s ladder down till we get to the last eigenvalue at which a next application of F + would produce an eigenstate with negative energy which we shall posutlate is not allowed and that must annihilate this last eigenstate ie F + E ↓ = 0 Aaaaghhhhh…… F+F+
73
They are F ± = q ± ip By inspection we can show that [H, F + ] = – ωF + [H, F – ] = + ωF – These are of the form [A, B] = kB So the Fs are B-type operators
74
Now H can be factorised as H = ½ω(F + F – – 1) H = ½ω(F – F + + 1) H = ½ω(F + F – – 1) H = ½ω(F – F + + 1)
75
Now H can be factorised as H = ½ω(F + F – – 1) H = ½ω(F – F + + 1) H{F + E n } = (E n – ω){F + E n } H{F – E n } = (E n – ω){F – E n }
76
Now H can be factorised as H F + E n = ½ω(F + F – – 1) F + E n H{F + E n } = (E n – ω){F + E n } H{F – E n } = (E n – ω){F – E n }
77
A A’ = A’ A’ AB A’ – BA A’ = kB A’ AB A’ – BA’ A’ = kB A’ A{B A’ } = (A’ + k){B A’ }
80
[A, B] = 0 If A and B commute there exist eigenfunctions that are simultaneously eigenfunctions of both operators A and B and one can determine simultaneously the values of the quantities represented by the two operators but if they do not commute one cannot determine the values of the quantities simultaneously
81
[A, B] = 0 [A, B] = k B A I A ’ › = A ’ I A ’ › A { B I A ’ › } = (A ’ + k ) { B I A ’ › }
82
[q, p] = i [H, q] = ω (-ip) [H, p] = ω (-iq)
83
F + = q + i p F − = q − i p [ H, F + ] = − ω F + [ H, F − ] = + ω F − H = − ½ ω ( F + F − − 1 ) H = + ½ ω ( F − F + + 1 )
84
H { F + I E n › } = ( E n − ω ){ F + I E n › } H { F − I E n › } = ( E n − ω ){ F − I E n › }
85
F + I E ↓ › = 0 H I E ↓ › = ½ ω I E ↓ › E (v) = ω (v + ½ )
86
F + = q + i p [H, q] = ω (-ip) F ± = q ± i p F − = q − i p [ H,F ± ] = q ± i p
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.